2015
DOI: 10.1002/cem.2711
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of smoothing techniques in the run to run optimization of fed‐batch processes with u‐PLS

Abstract: Run to run (R2R) optimization based on unfolded Partial Least Squares (u-PLS) is a promising approach for improving the performance of batch and fed-batch processes as it is able to continuously adapt to changing processing conditions. Using this technique, the regression coefficients of PLS are used to modify the input profile of the process in order to optimize the yield. When this approach was initially proposed, it was observed that the optimization performed better when PLS was combined with a smoothing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…In [21,30,31], it was suggested that the identified MVT be passed through a low-pass filter before being applied to the process. In this work, filtering the identified MVT proved to be beneficial and hence in each case study the MVT was passed through a zero-phase, low pass Finite Impulse…”
Section: Stagementioning
confidence: 99%
“…In [21,30,31], it was suggested that the identified MVT be passed through a low-pass filter before being applied to the process. In this work, filtering the identified MVT proved to be beneficial and hence in each case study the MVT was passed through a zero-phase, low pass Finite Impulse…”
Section: Stagementioning
confidence: 99%
“…A form of pseudo‐optimization in this class, which seeks to minimize the number of measurement pairs in x and y , is the design of experiments , central in chemometrics. Another typical example of data‐driven optimization is that used for process optimization, for instance in run‐to‐run optimization (see and references therein).…”
Section: Optimizationmentioning
confidence: 99%
“…The relay placement problem in ad‐hoc networks can be tackled with heuristic optimizations. In particular, Figure shows a comparison between PSO and the PLS optimization algorithm proposed in . This comparison was performed in a simulator based on MATLAB .…”
Section: Optimizationmentioning
confidence: 99%
See 2 more Smart Citations